2012
DOI: 10.1109/ted.2012.2205255
|View full text |Cite
|
Sign up to set email alerts
|

Interface-State Modeling of $\hbox{Al}_{2}\hbox{O}_{3}$ –InGaAs MOS From Depletion to Inversion

Abstract: This paper presents a detailed analysis of the multifrequency capacitance-voltage and conductance-voltage data of Al 2 O 3 /n-InGaAs MOS capacitors. It is shown that the widely varied frequency dependence of the data from depletion to inversion can be fitted to various regional equivalent circuits derived from the full interface-state model. In certain regions, incorporating bulk-oxide traps in the interface-state model enables better fitting of data. By calibrating the model with experimental data, the interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
90
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(98 citation statements)
references
References 8 publications
8
90
0
Order By: Relevance
“…5(a), 5(c), and 5(e), in all systems, we clearly see the presence of low bias peaks that disappear when increasing the excitation frequency. This observation is consistent with the presence of charge trapping into interface states [37]. At higher temperature, the electronic confinement of interface states can be thermally overcome as shown in Figs.…”
Section: Spinrasupporting
confidence: 88%
“…5(a), 5(c), and 5(e), in all systems, we clearly see the presence of low bias peaks that disappear when increasing the excitation frequency. This observation is consistent with the presence of charge trapping into interface states [37]. At higher temperature, the electronic confinement of interface states can be thermally overcome as shown in Figs.…”
Section: Spinrasupporting
confidence: 88%
“…A distance (x) for the spatial location of the border traps relative to the In 0.53 Ga 0.47 As interface can be estimated using the relationship 33 x ¼ k lnðt=sÞ; (7) where k is the attenuation coefficient and t is the tunnelling time. Assuming a k value within the typical range of 9.8 Â 10 À9 -1.25 Â 10 À8 cm reported for the Al 2 O 3 / In 0.53 Ga 0.47 As interface [16][17][18]21,30 and considering that N CP saturation is reached at t $ 5 ls (Fig. 6), we obtain a distance x of about 1.6-2.1 Å from the interface.…”
Section: Transient Charging Time and Border Trap Responsementioning
confidence: 72%
“…Recent studies have indicated the presence of border traps in high-k/InGaAs MOS structures using C-V, [15][16][17][18][19] charge pumping 20 and high-frequency transconductance 21 measurements. Evidence of the presence of border traps can also be observed in an I d -V g characteristic, where it is manifest as a hysteresis loop.…”
Section: B Evidence Of Border Trap Responsementioning
confidence: 99%
“…Fig. 9 shows the Dit profiles reported in the literature [10][11][12][13][14][15], which are compared to the effective density of interfacial states obtained by integrating the extracted N bt (E,z) along the oxide thickness, z, at any energy. The extracted effective Dit profile shows values comparable with those reported in the literature on similar devices.…”
Section: Resultsmentioning
confidence: 99%